English English - Monica, Novia Chris; Hasanuh, Nanu (2020)
This research objective was to identify effect of Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) partially and simultaneously on the Stock Price of Company. Data were collected from annual report of eight service companies listed in Indonesia Stock Exchange in the period of 2015-2018 in media, priniting, and advertising subsector. In analyzing data, it was used multiple regression analysis using hypothesis test and classical assumption test. The results show that there are significants effect of Return On Assets, Return On Equity and Earning Per Share on Stock Price while there is also simultaneously effect of Return On Assets, Return On Equity, and Earning Per Share on Stock Price.